Chemical constituents of Goniothalamus tapisoides / Rosalind Kim Pei Theng - Kim, Rosalind Pei Theng (2012)
Goniothalamus tapisoides Mat Salleh, a plant from Annonaceae family, has been studied. Collected from Sarawak, the bark of this plant were dried and grounded before phytochemical study was performed. The chromatographic separation on the dichloromethane extracts of the bark gave eleven compounds – six known and five new. Six known compounds were identified as goniothalamin 1, pterodondiol 164, liriodenine 114, 9-deoxygoniopypyrone 15, benzamide 161 and cinnamic acid 155. Five new compounds are goniomicin A 157, goniomicin B 158, goniomicin C 159, goniomicin D 160 and tapisoidin 162.